An Infusion Model for The Adoption of Social Media in Nigerian Tertiary Institution - Adebayo Idowu, Peter; Adefunke Oladejo, Racheal; Ademola Balogun, Jeremiah; Olusegun, Sarumi (purk, 2019)
This study aims to understand the trend of social media adoption among youths especially undergraduates of Nigerian tertiary institutions. This study used a questionnaire for identifying the various social media platforms. Also, the study formulated a polynomial function for estimating the number of students who will adopt the use of social media platforms based on the number of years after the year of social media adoption. The results of the study show that the social media platform adopted by Nigerian undergraduate students include: Facebook, Twitter, Instagram, SnapChat, WhatsApp, LinkedIn, WeChat, ResearchGate, Academia and Line. T
Keywords: Social media; Polynomial function; Best fit; Technology adoption; Infusion modeling